Pengaruh Kepemimpinan, Iklim Kerja dan Motivasi Terhadap Komitmen Pegawai pada Dinas Pendidikan Kabupaten Mandailing Natal - Heliyani, Heliyani; Ferriswara, Dian (Sekolah Tinggi Ilmu Ekonomi H. Agus Salim Bukittinggi, 2009)
Human resource concerning to civil government officer are one of the goverment official, employee of the country and employee of society, that have an important role in running organization and realizing organization purpose. To implement that duty, we need the condusif work climate and ability from a leader, motivation and good comitment from that employee self. This research have purpose (1). Getting empirical evident about how many the leadership effect, work climate and employee job motivation at Department of education in Mandailing Natal Regency. (2). Getting empirical evident about how many the leadership effect, work climate and job motivation at integrated condition to employee work commitment at Department of Education in Mandailing Natal Regency. Inthies research, the writter using double regression method, test t and test f. From the result, we can conclude that (1). There are significant effect from leadership to employee commitment at Department of Education in Mandailing Natal Regency. (2). There are significant effect from job motivation to independent variable give support to commitment about 62%.